Lecture Notes in Control and Information Science
DOI: 10.1007/11533382_14
|View full text |Cite
|
Sign up to set email alerts
|

Anticipative and Non-anticipative Controller Design for Network Control Systems

Abstract: Summary. We propose a numerical procedure to design a linear output-feedback controller for a remote linear plant in which the loop is closed through a network. The controller stabilizes the plant in the presence of delays, sampling, and packet dropouts in the (sensor) measurement and actuation channels. We consider two types of control units: anticipative and non-anticipative. In both cases the closedloop system with delays, sampling, and packet dropouts can be modeled as delay differential equations. Our met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Each sensor can calculate the terms it transmits using a recursive algorithm of the form outlined in equation (30). …”
Section: Theorem V2 In the Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Each sensor can calculate the terms it transmits using a recursive algorithm of the form outlined in equation (30). …”
Section: Theorem V2 In the Algorithmmentioning
confidence: 99%
“…The benefits incurred become even more apparent when the communication link is replaced by a network of communication links [15]. This effect can also be seen in the recent works on receding horizon networked control, in which a few future control inputs are transmitted at every time step by the controller and buffered at the actuator to be used in case subsequent control updates are dropped by the network and do not arrive at the actuator(s), see, e.g., [12], [13], [23], [29], [30].…”
Section: Introductionmentioning
confidence: 96%
“…The above theorem provides a matrix inequality that is linear in the design variables and , but suffers from the fact that the constraint is nonconvex. One appealing approach to deal with this was suggested in [32], [33], where the constraint is approximated with an optimization problem via the following lemma.…”
Section: Stabilizing the Closed-loop Systemmentioning
confidence: 99%
“…For such problems, El Ghaoui et al [32] showed that the nonconvex function can be replaced with a linear approximation for any given matrices and . With this insight, [32], [33] showed that an iterative algorithm can be used to minimize , while ensuring satisfaction of LMI constraints. For our application, the iterative approach proposed in those papers can be formulated as Algorithm 1.…”
Section: Stabilizing the Closed-loop Systemmentioning
confidence: 99%
“…This view was taken, e.g., in [10], [9], [12], [5]. This pre-processing strategy can also be seen in the recent results on receding horizon networked control, in which a few future control inputs are transmitted at every time step by the controller and buffered at the actuator to be used in case subsequent control updates are dropped by the network and do not arrive at the actuator(s) [6], [7], [16], [19], [20].…”
Section: Introductionmentioning
confidence: 95%